WATAK TOKOH PROTAGONIS GALA DALAM NOVEL GANJIL GENAP KARYA ALMIRA BASTARI - Sumiharti Sumiharti; Despita Sari. D (Universitas Batanghari, 2023)
This study aims to describe the character of the protagonist in the novel Ganjil Genap by Almira Bastari. This research is a qualitative descriptive research. The data in this study are in the form of sentence quotations in which there are characters of the protagonist Gala in the novel Ganjil Genap by Almira Bastari. The approach that the author uses in this research is a structural approach. The results of this study can be concluded that there are findings in the form of quotations related to 4 aspects of the character of the protagonist Gala in the novel Ganjil Genap by Almira Bastari. The four aspects are aspects of (1) honesty, (2) cleverness, (3) independence and, (4) loyalty to friends. From these four aspects, 55 quotations were found about the character of the protagonist. The most dominant quote found in the novel Ganjil Genap by Almira Bastari is the character of Gala's protagonist in the clever aspect of 18 quotes, and the least found is the character of Gala's protagonist in the loyal friend aspect of 6 quotes.